The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1123/jis.2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Is a Highly Successful Men’s NCAA Division II Cross Country Coach Humanistic? A Case Study

Abstract: The purpose of this case study was to investigate the coaching philosophy of a highly successful men's United States National Collegiate Athletic Association (NCAA) division II cross country coach and determine to what extent his stated philosophy and actual coaching methods were humanistic. For the past 13 seasons, the participant coach's men's cross country team has finished either first or second at the NCAA division II national championships. In-depth semistructured qualitative interviews of the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Research has shown that even in competitive environments, such as NCAA college basketball in the USA, coaches often place significant importance on realizing each athlete's potential, holistic development, and self-fulfillment. These aspects are considered essential parts of the definition of success in sport in these contexts [15]. Further research among coaches found that perceived success in sport includes the development of the players as a central component, followed by group performance, with victory only ranking in third place [16,17].…”
Section: Perceived Success In Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that even in competitive environments, such as NCAA college basketball in the USA, coaches often place significant importance on realizing each athlete's potential, holistic development, and self-fulfillment. These aspects are considered essential parts of the definition of success in sport in these contexts [15]. Further research among coaches found that perceived success in sport includes the development of the players as a central component, followed by group performance, with victory only ranking in third place [16,17].…”
Section: Perceived Success In Sportmentioning
confidence: 99%
“…The goals included athletic achievements, whereas success was not necessarily dependent upon this measure. Among other things, this discrepancy stems from a holistic perception of sport as providing education in values other than competitiveness [15,18]. This discrepancy has three possible explanations.…”
Section: Participants' Goals Vs Perceived Successmentioning
confidence: 99%